2017
DOI: 10.1055/s-0043-104690
|View full text |Cite
|
Sign up to set email alerts
|

Patienten zeigen sich zufrieden mit der Arzt-Patienten-Kommunikation – eine Pilotstudie mit dem „Individual Clinician Feedback“- Fragebogen

Abstract: The results of the pilot study are associated with a good response rate and patients were mostly very satisfied with the physician-patient communication. However, a selection bias among participating physicians is likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Patient satisfaction with regard to doctor–patient communication is recorded by the validated ICF questionnaire (Picker Institute Germany) 22 during a standard follow-up consultation 4 weeks after endoscopic inguinal hernia repair. The ICF questionnaire comprises 38 items concerning the patient’s experience of the examination atmosphere, the comprehensibility of the physician’s statements, the participation in decisions, the course of the conversation as well as sociodemographic characteristics of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction with regard to doctor–patient communication is recorded by the validated ICF questionnaire (Picker Institute Germany) 22 during a standard follow-up consultation 4 weeks after endoscopic inguinal hernia repair. The ICF questionnaire comprises 38 items concerning the patient’s experience of the examination atmosphere, the comprehensibility of the physician’s statements, the participation in decisions, the course of the conversation as well as sociodemographic characteristics of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the patient's satisfaction with the communication, another study (Commonwealth Fund) found out that doctor-patient communication was assessed as deficient [7,8]. Another study dealing with patient-centred communication [9] tried to gain insights into the doctor-patient communication within clinics from the patient's perspective and dealt with the examination atmosphere, the comprehensibility of the doctor's statements, and the involvement in the decisions and the course of the conversation.…”
Section: Introductionmentioning
confidence: 99%